Analisis Relevansi Praktik Pedagogis dan Literasi Digital Pada Pembelajaran Mendalam di SMK - Anita Herlina; Siti Yulianti; Erna Yayuk (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
Vocational education essentially emphasizes the development of practical competencies that are in line with the needs of the job market. To achieve deep learning, pedagogical practices in vocational education environments must integrate methodologies that increase student engagement and encourage interaction with learning materials and digital literacy. This study aims to analyze the relevance between teachers' pedagogical practices and students' digital literacy in supporting deep learning in vocational schools and the factors that influence it. The research method used was descriptive qualitative with the research location at SMKS Muhammadiyah 6 Rogojampi. The research subjects were mathematics teachers, curriculum coordinators, and 11th grade Light Vehicle Engineering students. Data were collected through interviews, student questionnaires, and documentation to obtain a comprehensive picture of the application of pedagogical practices and digital literacy skills in deep learning. The results of the study indicate that the pedagogical practices of teachers at SMKS Muhammadiyah 6 Rogojampi are quite relevant to the principles of deep learning, particularly in terms of encouraging active student engagement, digital literacy-based learning, and strengthening critical thinking skills. However, students' digital literacy levels still vary, with some students not yet optimally utilizing digital technology for knowledge exploration and collaborative learning. In addition, there are several key factors that influence the relevance of pedagogical practices and students' digital literacy, namely teachers' pedagogical and digital competencies, the readiness of school technology infrastructure, students' level of digital literacy, and support from school management. Significantly, this study shows that the relevance between pedagogical practices and digital literacy is key to developing deep learning in vocational schools. The successful implementation of deep learning in vocational schools is greatly influenced by teachers' ability to integrate reflective pedagogical approaches with the continuous strengthening of students' digital literacy.